Agama Digital (Digital Religion) dan Relevansinya Terhadap Studi Agama Interdisipliner: Sebuah Tinjauan Literatur - Maulana, Abdullah Muslich Rizal (At-Tafkir, 2022)
This article aimed to offer another side of the discussion concerning digital religion commonly understood as an interaction between technological users and religious phenomena on the screen or electronic devices, Digital Religion served as an interdisciplinary subject inviting multiple perspectives to reveal a more profound and comprehensive view regarding religious communities, expressions, and symbols in the digital world. This research was conducted as a literature review combining and analyzing massive lists of reputable references related to the topic. In addition, this research also utilized a content analysis method to summarize crucial ideas and information needed by the study. This paper concluded that Digital Religion emphasized the interaction between technology users and religious expressions in the digital world assisted by internet access. These interactions gave birth to new religious views, systems, and symbols different from conventional religious discourse. Moreover, it is apparent that Digital Religion was able to attract other branches of science to work together responding to issues, realizing it as an interdisciplinary study.